The Role of Honeypots and Sabotage in State-Based Operations Against Online Jihadism, 2001-2020 - Torres-Soriano, Manuel R. (Terrorism and political violence, 2023)
This article offers a descriptive analysis of intelligence operations carried out by the United States and its allies against the presence of jihadist groups on the Internet during the period 2001–2020. In contrast to actions aimed at eliminating the virtual spaces in which terrorists operate, the intelligence operations analysed here are designed to erode terrorists’ trust in such spaces without compromising intelligence sources. The article argues that the combination of cyberattacks and psychological operations in the form of honeypots and sabotage have achieved considerable success in terms of reducing terrorist activities on the Internet and undermining the effectiveness of propaganda initiatives undertaken by terrorist groups.